Análisis comparativo del impuesto de timbre en el Derecho Tributario de Colombia y el Derecho Tributario de Chile (2014)
The constant changes of the political, economic, social and international environment of a country for the globalization of the markets, it generates in the nations the need to adopt new models and changes in tax regulations, because with the entrance of the free trade agreement and other multilateral relations it is imperative to make the public administration more efficient, determining the increase or reduction of taxes and its application in the taxpayers The following research work articulated to the group “Comparative analysis of the national taxes of the Colombian tax lax and Chilean tax law” It has as an objective the comparative of the stamp duty between the tax law of the both South American Countries, analyzing the differences and similarities from the substantial and procedural frame. To understand how the collection of this tax is a representative income for the nations. To achieve the proposed, first off all we will describe the tax system in each country, then tax background will be checked updating its regulatory framework to get to the law that governs the tax, and finally to know the way of collection, its definition, the generating facts, who are the person in charge, how tax bases are calculated, to establish the exemptions and conditions of return of the tax, among other essential elements of the stamp.